Neurophysiological Studies May Provide a Misleading Picture of How Perceptual-Motor Interactions are Coordinated. (1st January 2013) - Mann, David; Dicks, Matt; Cañal-Bruland, Rouwen; Van Der Kamp, John
Neurophysiological measurement techniques like fMRI and TMS are increasingly being used to examine the perceptual-motor processes underpinning the ability to anticipate the actions of others. Crucially, these techniques invariably restrict the experimental task that can be used and consequently limit the degree to which the findings can be generalised. These limitations are discussed based on a recent paper by Tomeo et al. (2012) who sought to examine responses to fooling actions by using TMS on participants who passively observed spliced video clips where bodily information was, and was not, linked to the action outcome. We outline two particular concerns with this approach. First, spliced video clips that show physically impossible actions are unlikely to simulate a "fooling" action. Second, it is difficult to make meaningful inferences about perceptual-motor expertise from experiments where participants cannot move. Taken together, we argue that wider generalisations based on these findings may provide a misunderstanding of the phenomenon such a study is designed to explore.